1996
DOI: 10.1007/bf00051114
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin reduces restenosis after coronary angioplasty of high grade stenotic lesions: Results of SHIPS (SHIga Pravastatin Study)

Abstract: We conducted a multicenter prospective, randomized, double-blind, placebo-controlled trial to test whether pravastatin, a hydroxymethyl glutaryl coenzyme A reductase inhibitor, can decrease restenosis after percutaneous transluminal coronary angioplasty (PTCA). Pravastatin 10 mg twice daily was begun at least 10 days prior to elective PTCA in patients with total cholesterol less than 280 mg/dl. The end-point was a between-group comparison of the frequency of restenosis defined as a more than 50% loss of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Notably, with a single exception [74], all studies have reported a lack of significant effect for statins in preventing restenosis in human coronary arteries after PTCA or stenting. However, all of these studies have in fact shown a decreased neointima formation, with values ranging from 3% to 22% reduction in the rate of restenosis despite not achieving significance ( Table 1) [75][76][77][78][79][80][81][82].…”
Section: Clinical Studies On the Prevention Of Restenosismentioning
confidence: 99%
“…Notably, with a single exception [74], all studies have reported a lack of significant effect for statins in preventing restenosis in human coronary arteries after PTCA or stenting. However, all of these studies have in fact shown a decreased neointima formation, with values ranging from 3% to 22% reduction in the rate of restenosis despite not achieving significance ( Table 1) [75][76][77][78][79][80][81][82].…”
Section: Clinical Studies On the Prevention Of Restenosismentioning
confidence: 99%
“…While this finding suggests that hyperlipidemia may have been more prevalent in patients with recurrent restenosis, the frequency of cholesterol-lowering drug therapy was not an independent risk factor, as indicated by the results of multifactorial ANOVA in our study. Furthermore, although some reports have suggested that hyperlipidemia may be associated with an increased rate of restenosis after coronary angioplasty [30][31][32], other studies [33,34] did not confirm these results.…”
Section: Discussionmentioning
confidence: 86%